Valproate induces in vitro accumulation of long-chain fatty acylcarnitines - Silva, MFB (2015)
To elucidate the interference mechanisms of valproate (VPA) with mitochondrial fatty acid beta -oxidation (FAO), the profile of acylcarnitine formation was studied in vitro. Human fibroblasts were incubated with 0.2 mmol/L [U-C-13]palmitate, 0.4 mmol/L L-